Bound choice, election, and Wittenberg theological method: from Martin Luther to the Formula of Concord - Kolb, Robert (Lutheran quarterly books, 2005)
Galvanized by Erasmus' teaching on free will, Martin Luther wrote "De servo arbitrio", or "The Bondage of the Will", insisting that the sinful human will could not turn itself to God. In this first study to investigate the sixteenth-century reception of "De servo", Robert Kolb unpacks Luther's theology and recounts his followers' ensuing disputes until their resolution in the Lutheran churches' 1577 "Formula of Concord".